2020
DOI: 10.1101/2020.04.14.20064717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal Serum Concentrations of Selenium, Copper and Zinc during Pregnancy are associated with Risk of Spontaneous Preterm Birth: A case-control study from Malawi

Abstract: Preterm birth is delivery before 37 completed weeks. A study was conducted to evaluate the association of maternal serum concentrations of selenium, copper, and zinc, and preterm birth. There were 181 women in this nested case- control study, 90/181 (49.7%) term and 91/181 (50.3%) preterm pregnant women. The overall mean serum concentration of selenium was 77.0; SD 19.4microg/L, copper was 2.50; SD 0.52 mg/L and zinc was 0.77; SD 0.20 mg/L with reference values of 47-142microg/L, 0.76-1.59mg/L and 0.59-1.11 mg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…In the present study, no statistically significant association was found between maternal concentrations of Fe and the risk of SPTB, which was similar to an earlier report from a small birth cohort study in Australian women (33) and two studies from a prospective birth cohort in rural Bangladesh (24,38) . Besides, we did not observed a statistically significant association between the maternal concentrations of Cu and the risk of SPTB, which was consistent with four previous studies, a case-control study from Malawi about association analysis between maternal serum Cu and SPTB (37) , a prospective birth cohort in rural Bangladesh about the relationship between cord serum or maternal serum Cu and PTB (24,38) , and a nested case-control study in Beijing Birth Cohort (BBC), China, about association analysis between Cu concentrations in maternal hair and overall PTB as well as SPTB (21) . In addition, no statistically significant association was found between maternal concentrations of Zn and risk of SPTB, and this was similar to four previous study, including one analysis of maternal urine Zn concentrations and SPTB (32) , one study on maternal plasma Zn concentrations and SPTB (33) , one meta-analysis (39) , and another study on maternal serum Zn concentrations and SPTB (31) .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, no statistically significant association was found between maternal concentrations of Fe and the risk of SPTB, which was similar to an earlier report from a small birth cohort study in Australian women (33) and two studies from a prospective birth cohort in rural Bangladesh (24,38) . Besides, we did not observed a statistically significant association between the maternal concentrations of Cu and the risk of SPTB, which was consistent with four previous studies, a case-control study from Malawi about association analysis between maternal serum Cu and SPTB (37) , a prospective birth cohort in rural Bangladesh about the relationship between cord serum or maternal serum Cu and PTB (24,38) , and a nested case-control study in Beijing Birth Cohort (BBC), China, about association analysis between Cu concentrations in maternal hair and overall PTB as well as SPTB (21) . In addition, no statistically significant association was found between maternal concentrations of Zn and risk of SPTB, and this was similar to four previous study, including one analysis of maternal urine Zn concentrations and SPTB (32) , one study on maternal plasma Zn concentrations and SPTB (33) , one meta-analysis (39) , and another study on maternal serum Zn concentrations and SPTB (31) .…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported significant associations between the deficiency of trace elements and increased risk of PTB, or in other words, associations between the supplement of trace elements and decreased risk of PTB, including Fe (17)(18)(19)(20)(21) , Cu (22) , Zn (21,23,24) , Se (25)(26)(27)(28) and Sr (24) . However, some studies have revealed that the intake of trace elements were significantly associated with increased risk of PTB, including Fe (29)(30)(31) , Cu (31)(32)(33)(34)(35) and Zn (35)(36)(37) . In addition, other others have found no association between the levels of these elements and PTB, including Fe (24,33,38) , Cu (24,37,38) , Zn (31)(32)(33)39) , Se (21,(31)(32)(33)37,38,40) , Sr (31,35,38) and Mo (24,…”
mentioning
confidence: 99%
See 2 more Smart Citations